Immunogenetic Profiling of IL-6, IL-8, IL-18 and TLR4 Polymorphisms and Their Association with Breast Cancer Progression - Huseein, Farhan Khaleel; Mahdi Hassan, Ahamed; Najm, Hamzah Mahmood (Asian Pacific Journal of Cancer Biology, 2026)
Background: Breast cancer (BC) remains one of the leading causes of cancer-related morbidity and mortality in women worldwide. Although it has made great progress of early detection and treatment, the related immunogenetic mechanisms are still poorly understood. The present study sought to assess the immune molecular and genetic profile of several selected cytokines together with that of Toll-like receptor 4 (TLR4) in breast cancer patient women; their potential commitment on tumor progression and immune modulation. Materials and Methods: 65 women patients of breast cancer and same number of age matched healthy control were included in the study. The enzyme linked immuno-sorbent assay (ELISA) was used to measure serum concentrations of IL-6, IL-8, IL-18 and TLR4. The genetic background in cytokine and TLR4 pathways were analyzed for identification of candidate regulatory polymorphisms and pathophysiological significance in breast cancer etiology. All statistical analyses were performed using SPSS v26 with a level of significance p ≤ 0.01. Results: The study demonstrated significantly elevated serum levels of IL-6, IL-8, IL-18, and TLR4 in breast cancer patients compared to controls (p < 0.01). These findings suggest a strong immuno-inflammatory response and a possible activation of tumor-associated signaling pathways, including JAK/STAT, NF-κB, and TLR-mediated mechanisms. Polymorphisms in IL6, IL8, IL18, and TLR4 genes may influence cytokine expression and predisposition to tumorigenesis. Conclusion: The immune molecular dysregulation of cytokines and TLR4 appears to contribute to breast cancer progression through both inflammatory and genetic pathways. Integrating genetic polymorphism analysis with cytokine profiling could enhance diagnostic precision and support the development of personalized therapeutic strategies for breast cancer.